Supreme Irresolution and Peasant Autonomy: The totorales of Lake Titicaca - Orlove, Benjamín Sebastián (1991)
In the eighties, Peru experienced a severe economic crisis. But there were also, partly as a consequence of the crisis, important changes in the conceptualization of the national economy, both by "experts" (economists, high-level officials), and by many other sectors. A "second" Peruvian economy began to be part of official economic thought: the parallel, black, informal, alternative economy.